Program Employee Relations PT Citra International Underwrites ( CIU Insurance) Dalam Upaya meningkatkan Motivasi Kerja - Gan Gan Giantika (Jurnal Komunikasi, 2018)
Employees are one of the keys and long-term investments that can improve the development of the company and maintain the existence of the company. One of the factors that support to improve the company is the existence of good work motivation for employees. PT. Citra International Underwriters (CIU Insurance) experienced a decrease in work motivation caused by reduced communication between employees. As an effort to increase work motivation, PT Citra International Underwrites carried out a family gathering which was held on January 20, 2018 in the Taman Hutan Raya, Bandung, West Java. Family gatherings that are carried out successfully and employees can increase work motivation. In this study researchers used a qualitative approach and case study, as a research method that illustrates that by implementing a family gathering can improve good relations with employees so that employee motivation will increase. Keywords: Program, Employee Relations, Work Motivation